"Go See Somebody": How Spouses Promote Mental Health Care. (March 2020) - Reczek, Corinne; Thomeer, Mieke Beth; Gebhardt-Kram, Lauren; Umberson, Debra
This study considers when, whether, and how spouses encourage professional mental health care by analyzing qualitative data from 90 in-depth interviews with gay, lesbian, and heterosexual spouses. Findings show that a majority of spouses are engaged in promoting each other's mental health care but that the strategies used to promote care vary by gender and the gender composition of the couple. The majority of gay men and lesbian women promote care by framing mental health problems as largely biochemical, fixable only with professional care or medicine, and work to destigmatize this care. Lesbian women uniquely emphasize the influence of a spouse's symptoms on marital quality as a reason to pursue care. Some heterosexual women and men also report seeing their spouse's mental health care as something for them to deal with on their own and thus do not encourage care. This study has important implications for researchers looking to understand why some individuals seek mental health care and others do not and provides policymakers insight into mental health interventions via spouses.